POSISI EKSPOR-IMPOR INDONESIA DALAM MEA (SEBUAH STUDI KOMPARATIF) - Tria Apriliana (UNEJ e-Proceeding)
The aim of this study was to determine the position of Indonesia in facing Asean Economic Community (AEC) from the view of export and import compared to nine other member countries of AEC and to determine the difference between Indonesia’s export and import value before and after the implementation of AEC until the third quarter of the first year. Variables in this study was formed based on literature study. This study used secondary data, namely information related to import-export and in the Central Bureau of Statistics, World Bank, World Development Indicators and ASEAN Statistics. The comparative analysis of one-way ANOVA was used to test the differences in import-export  among the ten member countries of AEC and paired t-test was used to test the differences in import-export Indonesia before and after the implementation of AEC. The results of this study indicated that there are significant differences between export and import among ten member countries of AEC. The results also showed that there is no significant difference between Indonesia's exports before and after the enactment of AEC, but there are significant differences between the import of Indonesia before and after the implementation of AEC.